Salud e interculturalidad en Ecuador: las mujeres indígenas como sujetos de intervención de las políticas públicas - Mozo González, Carmen (Comparative Cultural Studies: European and Latin American Perspectives, 2017)
This text focuses on the analysis of the Intercultural Health Public Policy at Ecuador, using the Inter-Andean region of Ecuador as the empirical reference, and using the period in the beginning of the 1990s at the 20th Century as the timeframe. The aim is to show the conception and the location of indigenous persons in them, and in particular indigenous Ecuadorian women. To this end, we will focus on the “culturally appropriate childbirth”, a main action on these policies and, at the same time, an example of how indigenous women become intervention subjects in them. Specifically, we will deal with the case of the Hospital of San Luis in Otavalo, in the province of Imbabura, one of the most outstanding and publicized experiences of integrating "traditional medicine" into the National Health System, by the Ecuadorian government.